Multi-color-image compression-encryption scheme in the quaternion discrete Fresnel domain - Hu, Ze-Ting; Zeng, Ping-Ping; Ding, Hong-Xing; Gong, Li-Hua; Chen, Su-Hua (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
A multiple color images compression-encryption scheme is designed with compressive sensing in the quaternion discrete Fresnel transform. To tackle multiple color images in a holistic manner, the discrete Fresnel transform is extended into the quaternion domain and the images are encrypted with the quaternion discrete Fresnel transform. In this scheme, the RGB color components of plaintext images are simultaneously compressed and encrypted in three mutually independent channels. Then the red, green and blue components are scrambled respectively by a chaos sequence generated by the 2D logistic-sine-coupling map. Each color component matrix is compressed with sparse representation and matrix measurement. Subsequently, the compressed matrices are integrated into the quaternion algebras and re-encrypted by the defined quaternion discrete Fresnel transform. The devised nonlinear cryptosystem originates from the asymmetric phase truncation operation. In decryption, the original color images are reconstructed by the gradient descent with a sparsification algorithm. The proposed multiple color images compression-encryption algorithm is feasible, effective, secure and robust.
Optica Applicata, Vol. 54, 2024, nr 2, s. 259-276
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; compressive sensing; quaternion discrete Fresnel transform; 2D-LSCM chaotic system; image compression-encryption algorithm